PENERAPAN E-GOVERNMENT DALAM PELAYANAN PUBLIK DI KECAMATAN BUKIT RAYA KOTA PEKANBARU - Sutra, Dio Prama; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of e-government in the Bukit Raya District is the implementation of public services using information and communication technology in providing services to the community, this aims to facilitate administrative management, obtain information needed, involve public participation to encourage increased development as a form of public service transparency . This study aims to determine how the application of e-government in public services in the Bukit Raya District and its supporting and inhibiting factors. The theory used is aspects of the development of e-government by Indrajit namely three indicators that influence the implementation of e-government: Support, Capacity, and Value. This study uses qualitative research with a case study approach and the required data both primary and secondary obtained through observation, interviews and documentation techniques to further analyze the data with the interactive model of Miles and Huberman. The results of this study indicate that, firstly the implementation of e-government in public services carried out was optimal but not yet evenly distributed, these results were measured in terms of support, capacity and value. Second, the supporting factors for the implementation of e-government in public services in Bukit Raya District are human resources, facilities and infrastructure, while the inhibiting factors are socialization and network disruption.Â Keyword: Implementation, E-Government, Public Services